Die verband tussen die Christelike geloof en eensaamheid tydens laat-adolessensie - A. le Roux (Acta Theologica)
The nature and extent of the phenomenon of loneliness together with a related variable like the Christian faith, needs further investigation in order to unravel their scope and multidimensionality. The main aim of this investigation was therefore to determine whether the Christian faith and loneliness are related for late adolescents as is the case with adults (Le Roux 1998; 2000). The research group consisted of 154 first year students from the University of the Orange Free State. Their mean age was 19 years. The data were processed by means of the Pearson Product-Moment Correlation. The results firstly show that the Christian faith has a highly significant negative relationship with loneliness. Secondly, it was also evident that certain types of loneliness, viz religious, social, intrapersonal, communicative and emotional, relate very strongly with loneliness (p?0,01).